An ester bond underlies the mechanical strength of a pathogen surface protein - Hai Lei (Nature Portfolio, 2021)
Bacterial surface adhesion proteins are characterized by unusual mechanical properties. Here, the authors use atomic force microscopy-based technique to study a surface-anchoring protein Cpe0147 from Clostridium perfringens and show that an ester bond can withstand considerable mechanical forces and prevent complete protein unfolding.